Physical to biological building blocks in hand & microsurgery: the facts, the face, the facility, the field... and the future - Syed Waseem Ahmad, Sharifah Roohi (Universiti Putra Malaysia Press, 2018)
The Hand is a truly remarkable instrument - an organ of perception (feel, touch and much more), performance (power grip and fine motor functions), perspiration (sweating assists us in handling items and reducing body temperature), presentation and even communication. Second to the face the most commonly presented part of the body is the hand, thus its appearance of normalcy is crucial. Many a time when we are unable to verbalise our thoughts, we convey our messages, knowingly or otherwise, through non-verbal hand gestures as well as body language. Meanwhile, in dance forms and miming the hands are essential aspects of communication. Similarly sign language is basically that – an entire language communicated via the hands! Anatomically, due to the high density of nerve fibres at the fingertip, digits also aid in stereognosis which enables the blind to “see” and the deaf to “hear” (Alpenfels EJ 1955). The fact that the hand is structurally positioned at the extreme end of the upper limb, to enable it to reach out approximately one metre away from the body, however, makes it extremely susceptible to injury. Injury to the hand and wrist is devastating. All it takes is to imagine a day in one’s life without the right or even left hand. It becomes evident that a major portion of our lives and activities of daily living are dependent on us being able to have complete hand (and upper limb) function. In order for us to get through the day, there are numerous bimanual activities we perform without a thought. Even a minor papercut precludes us from continuing with these normally. Thus, hand injuries from the fingertip to the shoulder are functionally and emotionally distressing and need to be addressed immediately. Most importantly the injury or pathology needs to be treated right the first time. The Hand and Microsurgery field is a sub-specialty dealing with the treatment of conditions pertaining to the entire upper limb from fingertip to shoulder (Wikipedia). This includes both surgical and non-surgical management of congenital and paediatric conditions, trauma, infection, inflammation, haematological aspects, tumours, compression neuropathies, brachial plexus, the spastic hand, degenerative conditions and miscellaneous conditions such as Dupuytren’s and lymphatic anomalies. This relatively new sub-specialty of surgery developed rapidly in the 20th Century. The works of various researchers, clinicians and surgeons in this area brought about a conglomeration of discoveries which in themselves were remarkable but integrated together provided immense opportunities and ginormous developments. The most significant contribution of Sterling Bunnell, the Father of Hand Surgery, I feel, came in the form of a deep understanding of the intricate anatomy of the hand and its connection to function. He pioneered meticulous techniques, characterised by careful, detailed dissection with an eye on precision, leading to outstanding results, which he practically demonstrated by sharing his surgical techniques around the country (Green SA 2013). Developments in the 1960s, both mechanical and technical, allowed small diameter vessels (of 1 mm or less) to be repaired, opening up a plethora of possibilities and enabling various fields to collaborate for the betterment of the inflicted patient. Thus candidates from the fields of Orthopaedics, Plastic and General Surgery all enter this highly specialised field with the same philosophy: to repair, reconstruct and even replace. Great emphasis is placed on regaining function by therapy both prior to and after surgical or even non-surgical treatment. In the 70s and 80ss, as the field took off, anatomical discoveries of new flaps and arterial patterns and microsurgical refinement of the surgical application of these findings kept the momentum going and the excitement building. The birth of Reconstructive (Micro and even Supermicro – 0.3mm to 0.8mm diameter vessels) Surgery brought about new developments with the advances in transplantation medicine allowing amazing technical feats and repair of the human body. Another exciting area is that of biomedicine where the implant sizes are getting smaller, from mini to micro, and moving from surgical steel to Titanium and finally, bioabsorbable materials. Incisions are also reducing in size, assisted by arthroscopic equipment and innovative techniques. All are changing the way surgery is performed and raising the expectation bar higher. Currently however, we are moving slowly but surely to replacement not by physical means but by biological means, mainly rebuilding and regenerating lost tissue by chemical and biological options. Developing countries have both embraced this field as well found difficulties in implementing the finer aspects. Despite the costs being high and the learning curve steep, this has not deterred them. I feel that the excitement of discovering novel ways to tackle previously “impossible” cases has allowed this field of surgery to blossom. I shall discuss the origins of this subject and how it made an entry into our country (The Facts), both clinically as well as academically, the progress at present in terms of manpower development and what it takes to become a Hand Surgeon (The Face). This will be followed by the development of the infrastructure required to support it (The Facilities). The main essence will be examples of cases that have been seen and what needs to be addressed (The Field) as well as what I see for The Future in terms of prospects for upcoming surgeons and of course, the patients.